2022
DOI: 10.11591/eei.v11i3.3531
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian automatic short answer grading system

Abstract: Short answer question is one of the methods used to evaluate student cognitive abilities, including memorizing, designing, and freely expressing answers based on their thoughts. Unfortunately, grading short answers is more complicated than grading multiple choices answers. For that problem, several studies have tried to build an artificial intelligence system called automatic short answer grading (ASAG). We tried to improve the accuracy of the ASAG system at scoring student answers in Indonesian by enhancing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Technological progress leads to increasing research on automatic grading systems. Salim et al (2022) constructed a ridge regression model to enhance the accuracy of automatic short-answer grading systems for Indonesian language students by improving early state-of-the-art models and methods. The results demonstrated that the system using bidirectional encoder representations from transformer model and fine-tuning methods could enhance the accuracy of shortanswer grading [15].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological progress leads to increasing research on automatic grading systems. Salim et al (2022) constructed a ridge regression model to enhance the accuracy of automatic short-answer grading systems for Indonesian language students by improving early state-of-the-art models and methods. The results demonstrated that the system using bidirectional encoder representations from transformer model and fine-tuning methods could enhance the accuracy of shortanswer grading [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Salim et al (2022) constructed a ridge regression model to enhance the accuracy of automatic short-answer grading systems for Indonesian language students by improving early state-of-the-art models and methods. The results demonstrated that the system using bidirectional encoder representations from transformer model and fine-tuning methods could enhance the accuracy of shortanswer grading [15]. Abdul Salam et al (2022) proposed a hybrid approach that combined long short-term memory (LSTM) networks and grey wolf optimizer to automatically grade short-answer questions.…”
Section: Literature Reviewmentioning
confidence: 99%